Solid waste characterization study and management in Perlis - Norazura Binti Ahmad (School of Environmental Engineering University Malaysia Perlis, 2011)
This paper present a study of solid waste characterization and management in Kangar , Perlis. In order to identify wastes composition, the sampling was carried out based on the spot sampling method. whereas the laboratory analysis involved are moisture content analysis, thermo gravimetric Analysis (TGA) and calorific analysis via Bomb Calorimeter test. Altogether about 14 components of wastes had been evaluated and results shows three main constitutions of wastes generated are food waste, paper, plastic wastes. Then 8 out of 14 components had been identified as recyclable materials.